2015
DOI: 10.1021/acs.macromol.5b00759
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Viscosity Reduction and Hydrodynamic Interactions of Polymeric Nanocolloids in Polymers

Abstract: One of the central dogma of fluid physics is the no-slip boundary condition whose validity has come under scrutiny, especially in the fields of micro and nanofluidics.Although various studies show the violation of the no-slip condition its effect on flow of colloidal particles in viscous media has been rarely explored. Here we report unusually large reduction of effective viscosity experienced by polymeric nano colloids moving through a highly viscous and confined polymer, well above its glass transition tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 53 publications
(181 reference statements)
1
11
0
Order By: Relevance
“…3(c)) based mixtures, it can be observed that the η of PNCs with smaller f is comparably lower than the neat polymers, while the samples with higher f show a slight increase in η. Such reduction in the viscosity of PNC was observed earlier [7,[44][45][46] and alluded to the presence of thin interface layer surrounding the nanoparticles with reduced surface viscosity [7,44] Our earlier observations [31] also indicated the presence of an IL with reduced viscosity compared to the bulk. To quantify the temperature dependence of the observed viscosity, we have modeled the viscosity plots with VFT equation as given in eqn.…”
Section: Methodssupporting
confidence: 78%
“…3(c)) based mixtures, it can be observed that the η of PNCs with smaller f is comparably lower than the neat polymers, while the samples with higher f show a slight increase in η. Such reduction in the viscosity of PNC was observed earlier [7,[44][45][46] and alluded to the presence of thin interface layer surrounding the nanoparticles with reduced surface viscosity [7,44] Our earlier observations [31] also indicated the presence of an IL with reduced viscosity compared to the bulk. To quantify the temperature dependence of the observed viscosity, we have modeled the viscosity plots with VFT equation as given in eqn.…”
Section: Methodssupporting
confidence: 78%
“…8. Another very recent XPCS study by Begam et al on nanoparticle motion in thin polymer films observed greatly enhanced particle mobility, which the authors attributed to strong hydrodynamic interactions and slip at the particle-polymer interface [48].…”
Section: Xpcs Microrheologymentioning
confidence: 96%
“…In the past few decades, there have been many experiments measuring deviations from the no-slip boundary condition at microscopic length scales [1][2][3][4][5]. These measurements have stimulated the interest in hydrodynamic slip for both the fundamental understanding of the molecular mechanisms involved, as well as the impact of slip on technological applications [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
mentioning
confidence: 99%